A review of the sensitivity of metastatic colorectal cancer patients with deficient mismatch repair to standard-of-care chemotherapy and monoclonal antibodies, with recommendations for future research. (April 2021) - Wensink, Emerens; Bond, Marinde; Kucukkose, Emre; May, Anne; Vink, Geraldine; Koopman, Miriam; Kranenburg, Onno; Roodhart, Jeanine
Highlights: dMMR mCRC patients have decreased chemosensitivity versus pMMR mCRC patients. Different systemic non-immunotherapies show varying efficacy in dMMR mCRC patients. Insufficient data exists to definitively conclude which systemic agent is preferred. Meta-analysis of patient-level data may provide insight to guide optimal treatment. To optimize dMMR treatment, more representative preclinical models are needed. Abstract: In 5% of metastatic colorectal cancer (mCRC) patients, tumours display a deficient mismatch repair (dMMR) system. Immunotherapy is beneficial in dMMR mCRC patients and has recently been approved by the Food and Drug Administration for patients with unresectable or metastatic dMMR CRC. Although dMMR and proficient MMR (pMMR) CRC tumours are biologically distinct, they are commonly treated with the same chemotherapy and monoclonal antibodies. This includes dMMR mCRC patients who did not respond to immunotherapy (20–30%). However, it is unclear if these treatments are equally beneficial in dMMR mCRC. Of note, dMMR mCRC patients have a worse prognosis compared to pMMR, which may in part be caused by a lower response to treatment. To avoid unnecessary exposure to ineffective treatments and their associated toxicity, it is important to identify which systemic treatments are most beneficial in dMMR mCRC patients, thus improving their outcome. Indeed, future treatment strategies are likely to involve combinations of immunotherapy, chemotherapy and monoclonal antibodies. In this evidence-based review, we summarize clinical trials reporting treatment efficacy of different types of chemotherapy and monoclonal antibodies in dMMR mCRC patients. We also review the biological rationale behind a potential differential benefit of chemotherapy with or without monoclonal antibodies in dMMR mCRC patients. A barrier in the interpretation of preclinical results is the choice of model systems. They largely comprise traditional models, including cell lines and xenografts, rather than more representative models, such as patient-derived organoids. We provide concrete recommendations for clinical investigators and fundamental researchers to accelerate research regarding which systemic therapy is most effective in dMMR mCRC patients.